Pengaruh Motivasi dan Budaya Organisasi Terhadap Kinerja Karyawan Pada Inspektorat Jendral Kemendikbudristek - Ananda Melia Oktaviani (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
This study uses a quantitative statistical method through SPSS application calculations. The population in this study were 344 employees of the Inspectorate General of the Ministry of Education, Culture, Research and Technology, the sampling method used was the purposive sampling method with the slovin formula, obtaining a sample of 77 respondents. The analysis used in this study includes data quality testing, hypothesis testing, and determination coefficient testing. After conducting the hypothesis test, it is known that the t-test for motivation is 4.457> t-table 1.663 and the significant value is 0.000 <0.05, organizational culture t-test 1.341 <t-table 1.663 and the significant value is 0.184> 0.05, and the f-test is known that f- test 55.687> f-table 3.11 and the significant value is 0.000 <0.05. This proves that motivation partially influences employee performance while organizational culture does not influence employee performance, motivation and organizational culture simultaneously influence employee performance.